Shared growth urban renewal initiatives in Makati City, Metro Manila, Philippines - Michael V. Tomeldan; Mayla Antonio; Jocelyn Arcenas; Kristina Mae Beltran; Precious Anne Cacalda (Journal of Urban Management, 2014)
Urban renewal is a strategy for revitalizing underutilized and degraded sections of an inner city in the hopes of reducing crime, enhancing the environment, preventing further depreciation of land values, and stimulating economic activity. Many urban renewal projects in the past, however, have been associated with substantial demolition of properties, the displacement of residents, expensive infrastructure, and the gentrification of the urban renewal site. In this study, urban renewal schemes in Makati City, Philippines, are explored to determine the appropriate developments for identified urban renewal sites that are situated on the fringes of its affluent sections. The urban renewal proposals seek to involve the participation of the residents of the blighted areas so that they themselves can benefit from the revitalization initiatives. The conceptualized "shared growth" urban renewal initiatives will attempt to minimize dislocation, encourage investment, improve the urban environment, create a more vibrant neighborhood, and spread the economic benefits of the initiatives to the original residents of the redevelopment sites.
Keywords: 710; shared growth; sustainable urbanism; Urban renewal